The problem of the diagnosis of acute kidney injury in children operated under the conditions of artificial circulation - D. G. Balakhnin; I. I. Chermnykh; A. A. Ivkin; E. V. Grigoryev; D. L. Shukevich (Вестник анестезиологии и реаниматологии)
Acute kidney injury (AKI) associated with cardiac surgery in children is one of the most frequent complications of the postoperative period appearing due to various perioperative factors. Generally accepted criteria for the diagnosis of AKI, on the one hand, may underestimate the frequency of development of this complication, on the other hand, require verification for use in the pediatric population. The application of kidney injury markers in pediatric practice is associated with a number of difficulties. For example, the high variability of the concentration of markers depending on age complicates the interpretation of the result, and maternal molecules can circulate in the blood of newborns. At the same time, in the cardiac surgery practice, the greatest impact of the measurement of kidney injury markers in children has been noted, which allows significantly accelerate the diagnosis of this complication and the starting of its therapy.